Software clinic will treat NI firms. - Wojtas, Olga (Times Higher Education Supplement, 2002)
Reports the launching of a software initiative by Ulster University which can assess the strengths of software companies in Northern Ireland. Benefits of the initiative; Changes of the trends in the software industry.